GEOTECHNICAL SPECIFICATION OF AMERICAN AND KAZAKHSTAN STANDARDS IN PILE TESTING - Askar Zhussupbekov; Assel Tulebekova; Talal Awwad; Turlybek Mussabayev; Akmaral Tleubayeva (GEOMATE Journal, 2019)
Pile foundations become more essential during the construction of mega projects of the new capital of Kazakhstan–Astana. Many advanced pile technologies are appearing today. Unfortunately, Kazakhstan Standards have not a recommendation for modern pile design, testing and quality control methods. This paper presents methodic of the testing pile by ASTM D8169 (USA) standard and the State Standard 5686-94 (Kazakhstan). The methodic of testing piles by these standards have some differences. Discussion of using control equipment, technological features of the aforementioned methodic shall be important for the understanding of different points. The paper includes the results of piles of static tests using ASTM standards. The recommendations for the future modernization of Kazakhstan Standards have been given. It was concluded that the tests conducted according to the requirements of American standards which have made them more accurate and reliable.